AB0512 Biological treatment of still's disease. Report of seven pacients. (23rd January 2014) - Tejera, B.; Riveros, A.; Grados, D.; Martinez-Morillo, M.; Rodriguez, S.; Holgado, S.; Mateo, L.; Olivé, A.; Tena, X.
Abstract : Background: Still's disease is a rare systemic entity of unknown etiology, characterized by fever peaks with evanescent rash, arthritis and/or joint pain that is associated with odynophagia, lymphadenopathy and hepatosplenomegaly. Diagnosis is difficult and exclusion. Treatment has varied over time. Systemic glucocorticoidsare the first choice, although biological drugs are an alternative for refractory cases. Objectives: Describe the clinical characteristics and evolution of a series of patients diagnosed with Still's disease who have followed biological treatment. Methods: Retrospective (1978-2011). UniversityHospital with a referal area of 800, 000 inhabitants. We reviewed the medical records of patients from the database section of Rheumatology.Inclusion criteria: patients with Still' disease following Yamaguchi critera who were treated with biological drugs. Results: Seven patientswere selected: 5 women (71.5%) and 2 men (28.5%).The mean age at diagnosis was 30.2 (16-58).All hadsore throat, fever and allbut onerash.All hadpolyarthralgia. Six patients (85.7%) polyarthritis and one oligoarthritis.Four patients (57.1%) had splenomegaly, lymphadenopathy 2 of them (28.5%). Two patients did not have any of these clinical signs.Serositiswas foundonlyin one patient. Inlaboratory data yielded: leukocytosis with neutrophilia in 2 patients (28.5%), anemia (hb ≤12 g/dL in 3 patients (42.9%). Ferritinwas elevatedin two patients. The ESR was elevated in 4 cases (57.4%), with a mean of 45±39.53 mm in the first hour. The CRP was elevated in six patients (85.5%) with an average of 27.5 mg/L. Mean follow-up: 70 months. The form of evolution of the disease was polycyclic in 4 patients and monocyclic in three. Biological treatment was: anakinra in 5 patients (71.5%), etanercept, 2 patients (28.5%), tocilizumab, two patients (28.5%).In addition, one patient was refractory to all biologicals(infliximab, rituximab, anakinra, tocilizumab, abatacept). Three patients (60%) treated with anakinra achieved complete remission. The other two patients without remission, were treated with tocilizumab with a good response in one case. The remaining patientwas treated well with infliximab, rituximab, anakinra and tocilizumab. All treatments weerretired because of serious side effects or ineffectiveness. This patient is currently treated with abatacept with good response although is not achieving complete remission. The 2 patients treated with etanercept achieved complete remission. Conclusions: Biological therapy as treatment for refractory Still's disease was effective in most cases. Anakinra was the drug most widely used and more than half of patients who were treated with it, achieved complete remission. Disclosure of Interest: None Declared